O‘SMIRLARDAGI EMOTSIONAL INTELLEKT MUOMMOLARINING BOLALIKDAGI TO‘SIQLARGA BOG‘LIQLIGI - Alisherova, Z.T. (SCIENCE and SOCIETY, 2025)
In this article, the main cause of emotional intelligence problems in adolescence is explained by childhood obstacles. The emotional intelligence of adolescents in this period-empathy, self-acceptance, the ability to understand others, the ability to correctly assess and solve situations, the directions of their formation, and the manifestations of problematic behavior in interpersonal relationships It has been shown that the directions depend on childhood factors.